2020
DOI: 10.1109/access.2020.2976881
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Big Data-Based Research on the Influencing Factors of Insomnia and Spatiotemporal Evolution

Abstract: Insomnia is a prevalent sleep disorder that causes serious harm to individuals and society. It is closely linked to not only personal factors but also social, economic and other factors. This study explores the influencing factors and spatial differentiation of insomnia from the perspective of social media. This paper chose China's largest social media platform, Sina Weibo, as its data source. Then, based on the collected relevant data of 288 Chinese cities from 2013 to 2017, it explored the impact of economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…We believe that schools and parents should not excessively curb students’ use of mobile phones. Although previous studies have shown that the frequent use of mobile phones can cause a range of negative conditions ( Kumar and Anupama, 2019 ; Jacob, 2020 ; Liu et al, 2020b ), mobile phone use may also act as a kind of emotional sedative for some people (especially for neurotic individuals). It can be a tranquilizer that allows people to temporarily forget their worries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that schools and parents should not excessively curb students’ use of mobile phones. Although previous studies have shown that the frequent use of mobile phones can cause a range of negative conditions ( Kumar and Anupama, 2019 ; Jacob, 2020 ; Liu et al, 2020b ), mobile phone use may also act as a kind of emotional sedative for some people (especially for neurotic individuals). It can be a tranquilizer that allows people to temporarily forget their worries.…”
Section: Discussionmentioning
confidence: 99%
“…Through mobile phone use, individuals can establish and maintain a good social circle obtain social support ( Zhang et al, 2021 ) and sense of control in communication ( Volungis et al, 2020 ). On the other hand, prolonged mobile phone use may also bring about a lot of negative effects on college students physically and mentally such as anxiety and loneliness ( Kumar and Anupama, 2019 ; Jacob, 2020 ; Liu et al, 2020b ), sleep disorders ( Ma et al, 2022 ), poor school performance ( Gao et al, 2020 ) and so on. As a result, research on smartphone use is receiving increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…A social network is a suitable place for viral information. Although there are still fake news and negative impacts on social networks [ 22 24 ], social media is ideal for spreading positive information. It is also a popular tool to communicate and establish relationships between products/brands with their targeted customers [ 25 ].…”
Section: Related Workmentioning
confidence: 99%
“…The identification of prominent users in social networks s is a critical step in speeding up the spread of information, such as marketing applications, or preventing the spread of harmful content [ 27 ]. For users on a social network, the measuring of their impact on that network has been studied by many methods [ 22 , 28 ], such as: using association rules [ 29 ], nomological network [ 30 ], diffusion model [ 31 ]. Those methods can be classified as Local Measures [ 27 , 32 ], Short Path–Based Measures [ 33 ], Iterative Calculation–Based Measures [ 34 , 35 ], Coreness-Based Measures [ 36 ], and Machine-Learning Algorithms [ 37 , 38 ].…”
Section: Related Workmentioning
confidence: 99%
“…Finalmente, en un contexto mediado por el uso habitual y generalizado de las redes sociales para buscar amigos, compartir fotos, comprar bienes, escribir blogs, enviar mensajes, hacer videoconferencias, leer noticias, y pedir domicilios, entre muchas otras opciones, la social media representa en un escenario para el aprendizaje en red. Las redes sociales dan vida al aprendizaje al convocar diferentes personas y motivaciones en tiempos, espacios y posibilidades casi infinitas; este tipo de interacciones pueden apoyar la creatividad, la cooperación, la comunicación y el intercambio de información y recursos (Aldahdouh, Volumen Liu et al, 2020;Matassi & Boczkowski, 2020).…”
Section: Metodologías Activas Para El Aprendizajeunclassified